Outcomes with different administration schedules of bortezomib in bortezomib, lenalidomide and dexamethasone (VRd) as first‐line therapy in multiple myeloma. Issue 3 (13th January 2021) - Cook, Joselle; Johnson, Isla; Higgins, Alexandra; Sidana, Surbhi; Warsame, Rahma; Gonsalves, Wilson; Gertz, Morie A.; Buadi, Francis; Lacy, Martha; Kapoor, Prashant; Dispenzieri, Angela; Kourelis, Taxiarchis; et al.
Abstract: Induction therapy for multiple myeloma with bortezomib (Velcade), lenalidomide (Revlimid), and dexamethasone (d) (VRd) was traditionally administered as bortezomib given twice weekly on a 3 week cycle. A modified schedule of weekly bortezomib has been adopted over time to decrease treatment burden for patients and reduce treatment‐emergent neuropathy. This study evaluates the response rates and outcomes with different schedules of bortezomib in VRd administered for first‐line treatment for patients with newly diagnosed MM (NDMM). We retrospectively analyzed patients treated with upfront VRd from June 30th 2008 to December 31st 2018, for variations of bortezomib administration. Five hundred and fifty‐five (555) NDMM patients met inclusion criteria; median age 63 years and 61% men. Bortezomib was administered twice weekly every 21 days in 43%, once weekly every 21 days in 41% and once weekly every 28 days in 16%. Though peripheral sensory neuropathy was more frequent with twice weekly dosing ( P = .002), this group achieved shorter time to best response ( P = .01). Weekly every 21‐day treatment saw higher VGPR or better rates ( P = .02). However, with median follow up time of 37 months (IQR 22–56), we found no difference in PFS or OS among the groups. While small differences in response rates were found among the varying administration schedules of bortezomib administration, there was no significant effect on PFS or OS. Given that VRd remains a first line standard of care option for newly diagnosed MM, in the absence of a large trial comparing bortezomib dosing schedule modifications, these results are helpful in supporting current practices of once weekly administration.